Spin-off and market reaction: what is The Wall Street Journal role?. (2016) - Graziano, Elvira Anna
Building on the pioneering study by Covey (1999), this paper addresses a central question: according to the iceberg model of system thinking, can media play a relevant role in the financial market structure and hence influence the behaviour of investors? This study identifies specialised press as a key-player in the financial market. Through analysis with an event study approach, the effect of publication of spin-off news in The Wall Street Journal (WSJ) between 2000 and 2013 on the abnormal returns of 179 listed companies has produced the following results: 1) top newspapers seem to affect stock prices while not providing any new information, when publication follows the announcement; 2) top newspapers have a significant impact on the behaviour of investors, when the publication of news precedes the spin-off announcement.